The Influence of Financial Literacy, Pocket Money, and Lifestyle on the Financial Behavior of College Students who Use Online Shopping Platforms - Putri, Putu Devia Diandra; Lestari, Baiq Anggun Hilendri; Ridhawati, Rini (International Journal of Asian Business and Management, 2024)
This study aimed to determine the effect of financial literacy, pocket money, and lifestyle on the financial behavior of students who use online shopping platforms at the Faculty of Economics and Business, University of Mataram. This study uses primary data from questionnaires to 120 respondents who are active students of the Faculty of Economics and Business, University of Mataram, and students who use online shopping platforms such as Shopee and TikTok Shop. The method used is quantitative research with multiple linear regression analysis on the IBM SPSS software application version 25. This study concluded that financial literacy and pocket money positively and significantly affect the financial behavior of students who use online shopping platforms. This means that the better the understanding of financial literacy and the higher the amount of pocket money owned, the better the students' financial behavior. However, lifestyle does not affect students' financial behavior using online shopping platforms. This means that a high or low lifestyle does not affect students' financial behavior using online shopping platforms